THE MARKETING CONCEPT FOR MSME INDUSTRY BASED ON RETAIL COMMUNITY - CYNDIA AUDRIA SIANTURI; NALOM SIAGIAN MEDIA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
The reality of the growth of the retail industry, is actually a form of how there is growth in consumption growth in a modern format. In Indonesia, retail players such as Indomart and Alfamart are proof that the retail industry is in full bloom. The network is so tight, sticking together, shadowing each other. They exist in almost every district, with a strong franchise concept. On the other hand, by locus, they occupy an area, which is very likely in each region there is a small industry / MSME business that requires marketing links. This paper only intends to describe how the scenario for developing the MSME market is based on possible synergies with these retail companies. The result of reflection is the need for a driving aspect in the form of regulation by regional leaders and the readiness of MSME actors themselves when entering the modern retail network.